2021
DOI: 10.1101/2021.12.23.473936
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early life exercise primes the neural epigenome to facilitate gene expression and hippocampal memory consolidation

Abstract: Aerobic exercise promotes physiological and molecular adaptations in neurons to influence brain function and behavior. The most well studied neurobiological consequences of exercise are those which underlie exercise-induced improvements in hippocampal memory, including the expression and regulation of the neurotrophic factor Bdnf. Whether aerobic exercise taking place during early-life periods of postnatal brain maturation has similar impacts on gene expression and its regulation remains to be investigated. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 111 publications
(235 reference statements)
0
4
0
Order By: Relevance
“…We have used this method to compare transcriptomic data to epigenomic data from the same set of cells in an experiment to determine how voluntary aerobic exercise in early life might enable memory in adolescence (Raus et al., 2022 ). Fundamentally, using this transgenic mouse and this technique, we compared transcriptomic and epigenomic data from the same set of hippocampal excitatory neurons.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…We have used this method to compare transcriptomic data to epigenomic data from the same set of cells in an experiment to determine how voluntary aerobic exercise in early life might enable memory in adolescence (Raus et al., 2022 ). Fundamentally, using this transgenic mouse and this technique, we compared transcriptomic and epigenomic data from the same set of hippocampal excitatory neurons.…”
Section: Commentarymentioning
confidence: 99%
“…However, an animal expressing this cassette specifically in hippocampal excitatory neurons had yet to be generated. We study the interaction between epigenetic regulation and transcription in the brain after early life experiences (Raus et al., 2022 ), so we developed a mouse and a method to investigate these connected regulatory networks simultaneously. By crossing an Emx1 ‐Cre mouse (Gorski et al., 2002 ) with the NuTRAP mouse (Roh et al., 2017 ), we generated a transgenic mouse line that labels excitatory neurons in the hippocampus with both nuclear (mCherry and biotin) and ribosomal (GFP) tags.…”
Section: Introductionmentioning
confidence: 99%
“…We found that ICuRuS generated robust and reproducible H3K4me3 and H3K27me3 profiles at sufficient depth to examine cell-type specific chromatin from a single mouse striatum. These findings are an improvement over current methods, such as bulk tissue CnR 7,40 , which obscures cell-type specificity, and single-cell CnR, which requires pooled brain tissue and obscures subject variability 4,5 , a critical barrier given individual differences in stimulus-induced gene expression and susceptibility to psychiatric disease 33,[50][51][52] . Recent studies have applied FACS to isolate MSNs, but we found that the affinity purification strategy used in ICuRuS (and in the original INTACT protocol 9 ) potentially avoids FACS induced ectopic upregulation of activity dependent genes [53][54][55] .…”
Section: Discussionmentioning
confidence: 98%
“…Bulk tissue analysis reflects the average of cell-type specific changes, which impedes the interpretability of causal relationships between epigenetic modifications, regulation of gene expression and behavior 1-3 . Cell-type specific RNA-seq allows for the deconvolution of bulk tissue RNA-seq data, but cell-type specific epigenomic profiling in brain is only emerging [4][5][6][7] . Fortunately, recent methodological advances facilitate cell-type specific epigenetic profiling in brain [8][9][10][11] .…”
mentioning
confidence: 99%